1877 Mo. Laws 306, An Act To Provide for the Organization and Government of the Militia of the State of Missouri, Repealing All Other Acts and Parts of Acts Inconsistent with This Act, art. IV, § 3. - (:unkn) unknown (General Publisher, 1877)
A soldier who, unnecessarily or without orders from a superior officer, comes to any parade with his firearms loaded with ball, slug or shot, or shall so load the same while on duty, or unnecessarily or without orders from a superior officer, discharge the same, when going to or returning from or upon parade, shall forfeit not less than one nor more than five dollars.
--
Keywords: ARMED FORCES